Optical atomic clock aboard an Earth-orbiting space station (OACESS): enhancing searches for physics beyond the standard model in space. (1st January 2023) - Schkolnik, Vladimir; Budker, Dmitry; Fartmann, Oliver; Flambaum, Victor; Hollberg, Leo; Kalaydzhyan, Tigran; Kolkowitz, Shimon; Krutzik, Markus; Ludlow, Andrew; Newbury, Nathan; Pyrlik, Christoph; Sinclair, Laura; et al.
Abstract: We present a concept for a high-precision optical atomic clock (OAC) operating on an Earth-orbiting space station. This pathfinder science mission will compare the space-based OAC with one or more ultra-stable terrestrial OACs to search for space-time-dependent signatures of dark scalar fields that manifest as anomalies in the relative frequencies of station-based and ground-based clocks. This opens the possibility of probing models of new physics that are inaccessible to purely ground-based OAC experiments where a dark scalar field may potentially be strongly screened near Earth's surface. This unique enhancement of sensitivity to potential dark matter candidates harnesses the potential of space-based OACs.